Anti-cancer activity of synthetic gefitinib-1,2,3-triazole derivatives against Hela cells via induction of apoptosis - Hu, Zhihong; Hou, Xixi; Ren, Yongjing; Wu, Ziyuan; Yan, Dong; Chen, Hong; Wang, Lan (Frontiers in Chemistry, 2025)
Cervical cancer ranks as the fourth most common cancer among women. However, the current treatments have significant side effects and limited therapeutic effects on advanced diseases, so it is necessary to discover better treatments for cervical cancer. The current study investigated the potential anticancer effects of a series of gefitinib-1,2,3-triazole derivative on Hela cells. Among the investigated, the target compound c13 showed good anticancer activity against Hela cells (IC50 = 5.66 ± 0.35 μM) compared with gefitinib (IC50 = 14.18 ± 3.19 μM). Moreover, compound c13 significantly inhibited the colony formation ability of Hela cells in a dose-dependent manner, accompanied by morphological changes in HeLa cells. Further investigations demonstrated that compound c13 triggered cell apoptosis and arrested the cell cycle at the G2/M phase in Hela cells. In addition, western blot analysis revealed that compound c13 upregulated the Bax/Bcl-2 ratio, and increased the levels of active caspase 3 and PARP1 cleavage, which suggested the involvement of the mitochondrial pathway in compound c13-induced apoptosis. In brief, these results indicated that compound c13 is a promising compound for the treatment of cervical cancer.